Remittances, the diffusion of information and industrialisation in Africa - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2019)
This study examines the role of information and communication technology (ICT) on remittances for industrialisation in a panel of 49 African countries for the period 1980-2014. The empirical evidence is based on three simultaneity-robust estimation techniques, namely: (i) Instrumental Fixed Effects (FE) in order to control for the unobserved heterogeneity; (ii) Generalised Method of Moments (GMM) to account for persistence in industrialisation; and (iii) Instrumental Quantile Regressions (QR) to control for initial levels of industrialisation. Our best estimators are from FE and QR estimations because the GMM regression outputs largely fail post-estimation diagnostic tests. The following findings are established: (i) There are positive marginal effects from the interaction between remittances and ICT in the FE regressions whereas there are negative marginal impacts from the interaction between remittances and ICT; (ii) Interactions between remittances and mobile phone penetration are positive in the bottom and 90th quantiles whereas the interaction between internet penetration and remittances is positive in the bottom and top quantiles of the industrialisation distribution. Overall, the role of ICT in remittances for industrialisation is much more apparent when existing levels of industrialisation are accounted for. The findings contribute to the debates on the importance of external flows and information infrastructure in economic growth as well as the relevance of remittances in driving economic development in environments where institutions are weak. The value of the study to scholars and policy makers also builds on the fact that the potential for ICT and remittances in Africa can be leveraged to address development challenges on the continent such as the low level of industrialisation.
Keywords: F24; F43; F63; O30; O55; 330; Remittances; Industrialisation; ICT; Africa